Should Physicians Discuss Spiritual Concerns with Patients? - VandeCreek, Larry (Journal of religion and health, 1999)
The February, 1999 issue of The Lancet, a distinguished medical journal with worldwide circulation, contained an article titled, "Religion, Spirituality, and Medicine." It has received much attention. In one section of the article, the authors present three arguments against the popular opinion that physicians should give more professional attention to the religious and spiritual concerns of their patients. After briefly summarizing the article's material, I both endorse their position against physician discussion of religious materials with patients and provide three supplementary arguments. I argue that the popular notion that physicians should discuss religious materials with patients does not take adequate account of 1) the religious diversity among patients or 2) the lack of training and skills possessed by physicians. Additionally, it is inappropriate to recommend the involvement of religion or attention to spiritual concerns for health benefits.